O20 Dose-linearity of the pharmacokinetics of an intravenous [14C]midazolam microdose in children. Issue 6 (17th May 2019) - van Groen, BD; Vaes, WHJ; Park, BK; Krekels, EHJ; van Duijn, E; Kõrgvee, L-T; Maruszak, W; Grynkiewicz, G; Garner, RC; Knibbe, C; Tibboel, D; de Wildt, SN; et al.
Abstract : Background: Drug disposition in children may vary from adults due to age-related variation in drug metabolism, but paediatric pharmacokinetic (PK) studies are challenging. Microdose studies present an innovation to study PK in paediatrics, and can only be used when the PK of a microdose are dose-linear to a therapeutic dose. We aimed to assess dose-linearity of [ 14 C]midazolam (MDZ), a marker for the activity of the developmentally regulated CYP3A enzyme, by comparing the PK of an intravenous (IV) [ 14 C]MDZ microtracer given simultaneously with therapeutic MDZ, with the PK of a single IV [ 14 C]MDZ microdose. Methods: Preterm to 2-year-old infants admitted to the intensive care unit received [ 14 C]MDZ IV either as a microtracer during therapeutic MDZ infusion or as an isolated microdose. Dense blood sampling was done up to 36 hours after dosing. Plasma concentrations of [ 14 C]MDZ and [ 14 C]1-OH-MDZ were determined by accelerator mass spectrometry. A population PK model was developed with NONMEM 7.4 to study whether there was a difference in the PK of the microtracer versus those of a microdose [ 14 C]MDZ. Results: Of fifteen children (median gestational age 39.4 [range 23.9–41.4] weeks, postnatal age 11.4 [0.6–49.1] weeks), nine received a microdose and six a microtracer [ 14 C]MDZ (111 Bq/kg; 37.6 ng/kg). In a two-compartment PK model, bodyweight was the most significant covariate for volume of distribution. There was no statistically significant difference in any PK parameter between the [ 14 C]MDZ microdose or microtracer, suggesting the PK of MDZ to be linear within the range of the therapeutic doses and microdoses. Conclusion: Our data supports the dose-linearity of an IV [ 14 C]MDZ microdose in children, thus a [ 14 C]MDZ microdosing approach can be used to study developmental changes in hepatic CYP3A activity. Disclosure(s): This project was funded by the ZonMw ERA-NET PRIOMEDCHILD programme (projectnumber 113205022). * both authors contributed equally